2016
DOI: 10.1111/ajt.13863
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine and Risk of Skin Cancer in Organ Transplant Recipients: Systematic Review and Meta-Analysis

Abstract: Azathioprine, a purine antimetabolite immunosuppressant, photosensitizes the skin and causes the production of mutagenic reactive oxygen species. It is postulated to increase the risk of squamous cell carcinoma (SCC) and other skin cancers in organ transplant recipients (OTRs), but evidence from multiple, largely single-center studies to date has been inconsistent. We aimed to resolve the issue of azathioprine's carcinogenicity by conducting a systematic review of the relevant literature and pooling published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(110 citation statements)
references
References 86 publications
(173 reference statements)
0
110
0
Order By: Relevance
“…Observational studies have shown a significant association between azathioprine and skin cancer in the kidney transplant population 33 and in the inflammatory bowel disease population, 34 found a higher risk of all-cause mortality among sirolimus patients, but the proportion of cancer-related death was similar between the groups. 29 Based on the available evidence, cancer-related death is a significant issue amongst long-term kidney transplant recipients, and the use of mTORI has not been shown to modify this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown a significant association between azathioprine and skin cancer in the kidney transplant population 33 and in the inflammatory bowel disease population, 34 found a higher risk of all-cause mortality among sirolimus patients, but the proportion of cancer-related death was similar between the groups. 29 Based on the available evidence, cancer-related death is a significant issue amongst long-term kidney transplant recipients, and the use of mTORI has not been shown to modify this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant recipients use immunosuppressant medications to prevent organ rejection (3, 5). Some immunosuppressants have documented photosensitizing properties, and so elevations in KC risk may not be solely due to immunosuppression (9, 10, 20, 21). …”
Section: Discussionmentioning
confidence: 99%
“…Among transplant recipients, elevated KC risk may be driven by specific immunosuppressant medications, with particularly high risk observed among people taking azathioprine or cyclosporine (911). Immunomodulatory therapy has also been linked to KC incidence among people with rheumatoid arthritis or inflammatory bowel disease, two common autoimmune conditions (12).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, immunosuppression in SOTRs was predominantly maintained using cyclosporine and azathioprine 24 . A systematic review involving twenty-seven studies found a 56% increased risk of SCC development in SOTRs on azathioprine versus other immunosuppressants 29 . This is thought to be mediated by azathioprine induced skin hypersensitivity to UVA radiation and increased 6-thioguanine levels in DNA; both of which are thought to increase reactive oxygen species and subsequent SCC risk 30,31 .…”
Section: Discussionmentioning
confidence: 99%